KELAKUAN TANAH DENGAN SIFAT KEMBANG-SUSUT YANG TINGGI PADA STABILISASI TANAH DENGAN BAHAN SERBUK MARMER DAN BAHAN STABILIA - Ngurah Wardana, I Gusti (Jurnal Ilmiah Teknik Sipil, 2009)
Soil stabilization by adding limestone as admixture, was one of the most popular methods of chemical stabilization in Indonesia. However, with the development of soil stabilization method, stabilization using limestone has started to become unfeasible due to the increase of limestone price. Cheaper methods of chemical stabilization should be sought after. This alternative is apparent in the use of powdered marble, a waste from marble product processing factories which is relatively very cheap, and a new product called Stabilia as the only made-in Indonesia product of chemical stabilizer for soil with a price less than a third of that of the similar imported products. Research on the effectiveness of both powdered marble and Stabila as soil stabilizers is very limited. Therefore, in this study both of materials were tested on clay soil from Pejaten, Tabanan, in order to identify the changes of soil plasticity, the increase of the soil strength, the changes of soil swelling when the soil was submerged under water, the thickness of soil layer affected by water as a function of the submersion time, the effect of soil initial water content when being compacted toward its swelling and its compressive strength, and the optimum material. The specimens were made by adding powdered marble that ranges from 3% to 12% and the Stabilia content ranges form 0,3% to 3,0% of the total soil weight. From the test it was obtained that both materials caused reduction of soil swelling and increase of soil strength. In general, admixture with Stabilia presented better results in terms of free swelling and compressive strength of the samples. Apparently, Stabilia gave the performance almost similar to limestone stabilization. This study also gives a recommendation on the thickness of the soil layer to be stabilized and the optimum admixture content. It is also suggested that evaluation of the performance of stabilizing agent should not be based on the changes of soil plasticity alone, but it has to be determined according to the amount of allowable swelling, so that after the soil expands it is still able to support the load of foundation or vehicle tires. The influence of water submersion on the surface of the soil sample is merely felt at the relatively thin layer on the top of the sample.
Keywords: Stabilization, Soil, Stabilia